Perlindungan Hak Normatif Pekerja dalam Proses Industrialisasi - Teguh Sulistia (Jurnal Hukum IUS QUIA IUSTUM, 2003)
Protection of normative rights of the workers in Indonesia still weakness and necessary improve by government or labour organization. They treated dishonour by employer in work relationship on production process. Tripartite relationship is not running well too due government always to employers side than workers. Its impact, conflict between employer and workers can not to avoid. Harmonization and normative rights protection for workers.